Moyamoya disease and artery tortuosity as rare phenotypes in a patient with an elastin mutation. Issue 7 (15th April 2016) - Ishiwata, Tsukasa; Tanabe, Nobuhiro; Shigeta, Ayako; Yokota, Hajime; Tsushima, Kenji; Terada, Jiro; Sakao, Seiichiro; Morisaki, Hiroko; Morisaki, Takayuki; Tatsumi, Koichiro
Abstract : Sporadic and familial elastin mutations can occur in large vessel stenosis such as supravalvular aortic stenosis and narrowing of the descending aorta. However, there are very few reports regarding the arteriopathy of cerebral, pulmonary or abdominal arteries in elastin mutations. We herein report the case of a Japanese female patient presenting with multiple arteriopathy including moyamoya disease, a tortuosity of abdominal arteries and pulmonary hypertension due to peripheral pulmonary artery stenosis. This case suggests the possible progression of cerebral arteriopathy including moyamoya disease in patients with elastin mutations. © 2016 Wiley Periodicals, Inc.